Baker's cyst with extra‐ and intra‐articular synovial chondromatosis of knee: A case report - Sushant Kumar Khadka; Aashutosh Chaudhary; Suyash Acharya; Sagar Maharjan; Rohit Shrestha (Clinical Case Reports)
Abstract Synovial chondromatosis is a rare benign condition characterized by chondral proliferation from synovium forming loose bodies which can occur extra‐articularly and intra‐articularly. Surgical removal remains the mainstay of treatment for synovial chondromatosis. Due to the risk of recurrence, every case must be followed up with an MRI.